SAMAMBAIAS E LICÓFITAS DE FLORESTA DE TERRA FIRME NA COMUNIDADE JESUS MISERICORDIOSO, MUNICÍPIO DE BREVES, ESTADO DO PARÁ - BRASIL - BRABO, Daiane da Silva (2024)
The Microregion of Furos de Breves, Mesoregion of Marajó, has suffered major anthropogenic changes over the years. Thus, the present study aims to carry out a floristic survey of the species of ferns and lycophytes from terra firm forests occurring in the Jesus Misericordioso Community, in the municipality of Breves, state of Pará, in addition to providing information on the forms of life, the substrates in which they live, the preferred environments and the habitats of occurrence, thus expanding knowledge about the pteridoflora of Pará, in addition to enriching the collection of the Herbarium of the Faculty of Natural Sciences, Federal University of Pará, Campus do Marajó-Breves (CUMB) .The municipality is located in the Microregion of hole de Breves, consisting of rainforests, floodplains and capoeiras. Collections were carried out in the months of October, November and December 2022, January, April and October 2023. The samples were collected and herbalized according to the usual techniques for vascular plants. To identify the species, specialized bibliography was used and samples deposited in the UFPA CUMB herbarium were consulted, with the testimonial material being incorporated into its collection. 16 families (two lycophytes), 27 genera and 54 species (3 lycophytes and 51 ferns) were recorded. The families with the highest specific richness were Hymenophyllaceae (11spp.), Pteridaceae (9spp.), Polypodiaceae (6spp.) and Dryopteridaceae (5spp.). The most representative life forms were epiphytes (25spp.) and terrestrial (19spp.), with Cyclodium meniscioides (Willd.) C. Presl, Nephrolepis rivularis (Vahl) Mett. ex Krug and Triplophyllum funestum (Kunze) Holttum occurred both terrestrially and epiphytically. As for the substrate, (22spp.) occur on living trunks and (19spp.) on the soil. The environment with the greatest species richness was the interior of the forest (33 spp.), 11 were recorded on the edge of the forest and ten occur in more than one environment. Most species occur in areas considered preserved (32spp.) while (8spp.) occurred in both altered and preserved areas. The area analyzed, despite being impacted by anthropization, presents a considerable floristic composition, with the record of species rarely found in the forests of the state region, such as Elaphoglossum obovatum Mickel, Oleandra articulata (Sw.) C.Presl, O . pilosa Hook., Selaginella parkeri (Hook. & Grev.) Spring, Trichomanes accedens C. Presl,T. cristatum Kaulf., T. tanaicum Hook. ex J. W. Sturm, T. tuerckheimii Christ and Triplophyllum angustifolium Holttum.